ETHICAL GUIDELINES FOR USING AI IN ONLINE HADITH STUDIES - Mesbahul Hoque; A. Irwan Santeri Doll Kawaid; Shumsudin Yabi, (International Prophetic Conference (SWAN) FPQS USIM, 2024)
The advent of Artificial Intelligence (AI) has revolutionized various fields, including religious studies, where it offers new methodologies for studying and analysing religious texts, such as Hadith. Hadith, which are the recorded sayings and actions of the Prophet Muhammad SAW, serve as crucial sources for Islamic jurisprudence and ethics. However, the integration of AI in Hadith studies raises significant ethical concerns that scholars must address to ensure respectful and accurate engagement with these sacred texts. Using analytical method, this study aims to highlights on some ethical guidelines for the use of AI in Hadith studies to ensure the responsible and respectful application of artificial intelligence in the field of Hadith. The result of study shows that, it is essential to emphasize the importance of human oversight and critical thinking in conjunction with AI technologies to avoid misinterpretations or misrepresentations of Hadith texts.